Japan's Legal Education Assistance in Asia: Building a Cohort of Jurists for Transition Reforms. (January 2021) - Ismatov, Aziz; Makino, Emi
For about three decades, Japan has been providing legal assistance to select countries in Asia in their transition endeavours from socialism to market economy. Whereas historically, international legal assistance traditions and their philosophies were designed by Western donors, Japan intends to demonstrate a shift from such traditional settings by offering its own ideas and approaches towards legal development in Asia. Among features such as request-based approach, prioritization of local culture and society in legal assistance, and supreme national interests in providing Official Development Assistance (ODA), Japan places a particular focus on human recourses development in Asia. This research article on the concrete example of Nagoya University will focus on Japan's legal education assistance initiative to foster human resources in Asian countries of Uzbekistan, Mongolia, Vietnam, Cambodia, Myanmar and Laos. By focusing on educational projects of Nagoya University, which many refer to as the Asian hub for legal education, this article will shed light on the nature, primary objectives and challenges of nurturing future legal specialists as proposed by Japan's broader legal assistance initiative in Asia. This article asserts that the goal of the Japanese legal education project is not necessarily to export Japanese law and theory to Asian recipient countries but to enable future Asian jurists to understand own law or the foreign legal systems in comparative perspective and teach skills to independently and adequately address future legal challenges arising in own country.